FUNCTIONAL LONGEVITY INTEGRATED CARE FRAMEWORK (FLICF™): A MULTIDISCIPLINARY MODEL FOR HEALTHY AGING, FUNCTIONAL INDEPENDENCE, AND HEALTHCARE SUSTAINABILITY - Aymay , Karin (RCMOS - Revista Científica Multidisciplinar O Saber, 2026)
Background: Population aging is transforming healthcare systems throughout the United States. Although advances in medicine and public health have significantly increased life expectancy, aging populations continue to experience rising rates of chronic disease, functional decline, falls, disability, healthcare utilization, and demand for long-term support services. Simultaneously, healthcare workforce shortages and rising healthcare expenditures pose additional challenges to healthcare sustainability. Existing healthy aging initiatives frequently address these issues through isolated interventions rather than integrated, function-centered models. Objective: To introduce the Functional Longevity Integrated Care Framework (FLICF™), a multidisciplinary conceptual model designed to preserve functional independence, promote healthy aging, and support healthcare sustainability through coordinated healthcare interventions. Methods: This study utilized a narrative literature review combined with a conceptual framework development methodology. Scientific literature, governmental reports, public health publications, workforce analyses, and healthy aging initiatives were reviewed to identify recurring determinants of healthy aging and healthcare sustainability. Findings were synthesized with more than twenty-two years of professional clinical experience across intensive care, rehabilitation, home healthcare, and community-based healthcare settings. Results: The review identified five interconnected domains associated with healthy aging and preservation of functional independence: Early Functional Assessment, Preventive Rehabilitation, Integrated Home-Based Healthcare, Post-Discharge Continuity Programs, and Healthcare Workforce Development. These domains were integrated into the Functional Longevity Integrated Care Framework (FLICF™), a model centered on Functional Longevity, defined as the preservation of mobility, independence, participation, resilience, and quality of life throughout the aging process. Conclusion: The FLICF™ provides a novel multidisciplinary framework that shifts healthcare priorities from a predominantly disease-centered model toward a function-centered approach. By integrating prevention, rehabilitation, continuity of care, home-based healthcare, and workforce preparedness, the framework offers a scalable strategy to address population aging, support aging in place, reduce preventable disability, and improve healthcare sustainability. Future implementation studies are needed to evaluate effectiveness, cost-effectiveness, and scalability across diverse healthcare environments.